"Participation" in the internationalized higher education classroom: An academic staff perspective. Issue 3 (3rd July 2018) - Murray, Neil; McConachy, Troy
ABSTRACT: For universities seeking to promote internationalization, the development of an understanding and appreciation of cultural diversity among staff and students is a priority. Cultural and linguistic diversification of the student body can, however, present academic staff with challenges in the areas of curriculum, teaching methods and assessment. In this study, we take up the culturally variable notion of "participation" as a constituent of learning and draw on data derived from focus group interviews to probe the participation-related challenges reported by academic staff in a UK university. Finally, we consider the implications of our findings for strategic interventions aimed at academic staff.